Cloud Based Data Analytics: A Review - Arundhati Dhar; Mayank Tiwari (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Large volumes of data are generated every second from various sources like social networking platforms, IoT (Internet of Things), sensory devices, wireless communications services, ecommerce platforms, government agencies, to name a few. Regular data processing paradigms yield insignificant results while dealing with data of such large volumes, and are consequently labeled as Big Data. Big Data is a blanket terminology that deals with the storage, management, processing, and most importantly, the analyzing of such data. Cloud Computing has emerged as a technology of paramount importance to modern computing, and deals with providing the infrastructure and computing resources required for such processes in an efficient and cost-effective manner. Various sectors including healthcare, education, and government agencies, are leveraging Big Data to improve decision-making. For example, the medical industry is making use of Big Data to better understand their patients and develop personalized treatment plans, while government agencies are using it to track and prevent fraud, waste, and abuse. This paper presents an in-depth description of cloud computing and big data. We then delve into Big Data analytics where we discuss various Big Data paradigms, and introduce Big Data analytics in the context of cloud computing. Lastly, we discuss the advantages of using Big Data analytics in Cloud Computing as well its limitations and future enhancements for this vast domain.